The role of cryptic Mastomys rodents in the maintenance and transmission of encephalomyocarditis virus in southern Africa - Bastos, Armanda D.S. (University of Pretoria, 2024)
Dissertation (MSc (Zoology))--University of Pretoria, 2024.